FRI0197 Association of the electrocardiographic disturbances with aortic root dilation in patients with ankylosing spondylitis. (12th June 2018) - Park, H.S.; Laiz, A.; Alonso, C.; Jeria Navarro, S.; García-Guillén, A.; Millan, M.; Moya, P.; Magallares, B.; Castellvi, I.; Diaz-Torne, C.; Fernandez, S.; Casademont, J.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a disease with very characteristic extraarticular organ involvements. Cardiac conduction disturbances and aortic root diseases are some of the most particular manifestations of this disease¹. The most frequent conduction disturbances are atrioventricular blocks (AVB), bundle branch blocks (BBB) and intraventricular conduction disturbances (IVCD)². The prevalence of AVB is 3% and 8% for IVCD in the general population³. In some cross-sectional studies of the AS population 4, 5 the prevalence was reported to be around 4.6%–9% for AVB and 4%–29% for IVCD. Some studies propose that there may be a relation between the conduction disturbances and the inflammation of the aortic root due to disease activity 6, 7, 8 . Objectives: This study aims to evaluate association between the electrocardiographic alterations (AVB, BBB, IVCD) and aortic root dilation in patients with AS. Methods: Out of a registry of 118 patients from a spondyloarthritis consultation, we selected patients with AS according to New York criteria. We included those patients who had underwent an electrocardiography (EKG) and an echocardiography, in ordeer to rule out heart disease or to check up because of long term AS. Demographical and clinical data (cardiovascular risk factors, past heart disease, presence of arthritis, enthesitis, dactylitis, uveitis and HLAB27) were collected. The EKG were reevaluated looking for IVCD, AVB or BBB by a blinded arrhythmologist. Echocardiographical data about aortic root dilation were collected using aortic root diameter adjusted by body surface area. We carried out chi squared analysis as well as a comparison of proportions. We summarised descriptive data of our sample in table 1. Results: Out of 118 patients, 38 patients met inclusion criteria. Fourteen of them (36.8%) were women. The average age was 60.3 years old and mean disease duration was 19.62 years. Conduction disturbances was present in 12 (31.5%) patients of whom 4 were AVB (10.5%), 5 BBB (13.2%) and 3 IVCD (7.8%). Aortic root dilation was found in 6 (15.8%) of the 38 patients. The conduction disturbances showed a statistically significant association with aortic root dilation (chi square p=0.02). In comparison of two proportions, the prevalence of aortic root dilation in abnormal EKG group (0.67 IC95% 0.36%–0.97%) was significantly higher than normal EKG group (0.6 IC95% 0.36–0.97) p=0.02. Conclusions: The prevalence of aortic root dilation and conduction disturbances was higher in our sample than in the general population. In our sample the presence of aortic root dilation and conduction disturbances (AVB, BBB, IVCD) had a statistically significant association. The principal limitations of this study are the small sample size and the retrospective nature in patient selection. References: [1]. ARD 2018;0:1–8. [2] Am J Cardiol2017;120:2226–2232. [3] Rev Esp Cardiol2005;58(6):657–65. [4] BMC Muscul Dis2013;14:237. [5] Scand J Rheumatol2010;39:38–41. [6] Joint Bone Spine2011;78:451–455. [7] Clin Rheumatol2015;34:995–998. [8] Arth and Rheum2016;68:2476–2486. Disclosure of Interest: None declared